2011
DOI: 10.1002/jmv.22168
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the signal‐to‐cutoff ratios of hepatitis C virus antibody screening tests used in China

Abstract: The clinical diagnosis of hepatitis C virus (HCV) infection is important to direct an accurate course of therapy. Previous studies have reported a correlation between the signal-to-cutoff (S/CO) ratios of the anti-HCV screening test and confirm HCV infections for American anti-HCV screening kits as well as for those in China. It is currently unknown whether clinical laboratories use the same threshold S/CO ratios under routine conditions and if these values are acceptable for the analysis of Chinese samples. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…We speculated that the low prevalence of HCV RNA among anti-HCV-positive patients could be due to the high false-positive rate of the used assay for anti-HCV (Architect reagents). With this method, false-positive results have been found in about 95% of the initial positive results with S/CO values less than 5 [ 25 ], which accounted for around one third (185/570) of the subjects recruited in this study, indicating a low prevalence of HCV RNA in the cohort.…”
Section: Resultsmentioning
confidence: 99%
“…We speculated that the low prevalence of HCV RNA among anti-HCV-positive patients could be due to the high false-positive rate of the used assay for anti-HCV (Architect reagents). With this method, false-positive results have been found in about 95% of the initial positive results with S/CO values less than 5 [ 25 ], which accounted for around one third (185/570) of the subjects recruited in this study, indicating a low prevalence of HCV RNA in the cohort.…”
Section: Resultsmentioning
confidence: 99%
“…In an attempt to ensure a higher PPV, higher thresholds for the S/CO values were considered. This approach has been employed in many previous studies on anti-HCV, and most of them have indeed demonstrated the relationship between high S/CO values and serological confirmation of anti-HCV positivity (9,(14)(15)(16)(17) and even with HCV viremia (14,18). Thus, a higher S/CO ratio for anti-HCV is deemed to guarantee a higher PPV, but the data on the other screening assays are less common (10,11,19), and we believe that ours is one of the first systematic attempts in this direction, although it has been carried out on a relatively small number of blood donations.…”
Section: Discussionmentioning
confidence: 99%
“…RIBA is still widely used in countries other than the United States due to its cost effectiveness [3][4][5]. In the present study, samples with an S/Co between 1 and 10 tested with Elecsys Anti-HCV II assay were mostly falsepositive by RIBA.…”
Section: Discussionmentioning
confidence: 58%
“…Current CDC guidelines suggest the use of assay-specific signal-to-cut-off (S/Co) ratios as anti-HCV confirmation to limit the number of samples needing supplemental testing [1,2]. Nevertheless, RIBA is still commonly used in other countries, including China [3][4][5].…”
Section: Introductionmentioning
confidence: 99%